The Effect of Emodin-Assisted Early Enteral Nutrition on Severe Acute Pancreatitis and Secondary Hepatic Injury - Gang Wang; Bei Sun; Yue Gao; Qing Hui Meng; Hong Chi Jiang (Mediators of Inflammation)
Severe acute pancreatitis (SAP) characterized by atrocious progression and numerous complications often leads to a high mortality rate due to hypermetabolism, systemic inflammatory response syndrome (SIRS), and multiple organs dysfunction syndrome (MODS). Studies have revealed that both early enteral nutrition (EEN) and emodin are potent agents in the management of SAP. However, whether the combined strategy is rational and more effective than either one alone remains unknown. In this regard, Wistar rats were treated with emodin-assisted EEN (EAEEN) through enteral nutrient tubes after induction of SAP by retrograde infusion of 5.0% sodium taurocholate into the common pancreatic duct. Serum levels of amylase, tumor necrosis factor-alpha (TNF-α), angiotensin II (AngII), maleic dialdehyde (MDA), glutamic pyruvic transaminase (ALT), glutamic oxaloacetic transaminase (AST) and C-reactive protein (CRP), intestinal secretory IgA (SIgA), pancreatic and hepatic myeloperoxidase (MPO) activity as well as plasma levels of D-lactate and endotoxin were measured. In addition, pathologic alterations of pancreas and liver were observed microscopically. We found that EAEEN could significantly ameliorate these parameters and prevent pancreas and liver from serious damage. In conclusion, Our results indicated that EAEEN could exert beneficial effects on experimental SAP and obviously abate the severity of secondary hepatic injury. The combined strategy was safe and more effective than either one alone in the acute stage of SAP. This study also provided an experimental base for the clinical treatment of SAP patients with EAEEN.